The Evolution and Dynamics of Social Entrepreneurship: Bridging Innovation, Sustainability, and Societal Impact - LAHMIDI , Wiam; NEFZI , Nouhaila; ZINE-DINE , Khaoula (Revue Internationale des Sciences de Gestion, 2025)
This literature article explores the evolution, definitions, and core principles of social entrepreneurship, emphasizing their roles in addressing societal and environmental challenges. The purpose of this literature review is to synthesize existing research on the conceptual and practical development of social entrepreneurship, identify its key milestones, and examine the interplay between social entrepreneurship and social enterprises. Methodologically, it draws on seminal works and recent studies to analyze the economic, social, and governance dimensions of social enterprises, highlighting their distinct operational frameworks and participatory dynamics. The findings reveal that social entrepreneurship has matured into a professionalized field, with innovative frameworks and institutional support. However, gaps remain in measuring long-term social and environmental impact and understanding how social enterprises sustain systemic change. This review provides a foundation for further exploration into the scalability of social entrepreneurship and its potential to address pressing global challenges.